Enhancing Employee Engagement and Productivity in Technology Companies through Digital Gamification - Idam Wahyudi; Anggun Sulistyowati; Parviz Hasanov (International Forum of Researchers and Lecturers, 2024)
This study investigates the impact of digital gamification on employee motivation, engagement, and productivity in technology companies. Gamification, which integrates game design elements such as rewards, badges, and leaderboards into non-game environments, has gained popularity as a tool for enhancing employee performance in workplaces. The research employs a quantitative survey methodology to gather data from employees in technology firms that have implemented gamified systems. The findings reveal that gamification significantly increases employee motivation by tapping into intrinsic motivators such as autonomy, competence, and relatedness. Employees reported higher levels of engagement, with many attributing their increased participation to the fun and competitive nature of gamified tasks. Additionally, productivity improvements were observed, particularly among employees in roles that require individual performance, such as software engineers, where autonomy and goal-setting were key factors. The study also identifies variations in the effectiveness of gamification based on factors such as job role and organizational culture, emphasizing the need for customization to suit different employee needs. Despite these positive outcomes, challenges such as employee resistance, poorly designed systems, and resource constraints were noted as barriers to successful gamification implementation. These findings suggest that gamification is an effective strategy for improving motivation and engagement in technology companies but requires thoughtful design and alignment with company culture to maximize its impact. Future research should explore the long-term effects of gamification and examine how specific elements, such as leaderboards and rewards, influence employee behavior across different demographics.